Biotic and abiotic constraints to Stylosanthes production - Kelemu, Segenet; Miles, John W.; Rao, Idupulapati M. (Australian Centre for International Agricultural Research, 2004)
The genus Stylosanthes Sw. has provided ample germplasm for a wide variety of agroecological situations in the tropics. The most important attributes of successful Stylosanthes cultivars used as pasture or ley in the tropics are resistance to diseases, high seed yield and adaptation to poor soils. This chapter reviews work conducted on the biotic and abiotic limitations to Stylosanthes production, and discusses management strategies to combat some of these limitations.